Strategies that Support Kindergarten Children's Social and Emotional Development: One Teacher's Approach. Issue 1 (March 2017) - Kirk, Gillian; MacCallum, Judith
THIS ARTICLE EXAMINES THE strategies employed by one kindergarten teacher, Kyra, to create a classroom where the relationships, play situations and environments worked synergistically to support children's social and emotional competencies. The data is drawn from a larger study, undertaken in 2009, that used qualitative methodology to examine how teachers were supporting kindergarten children's social and emotional development. Out of the eight participants from the original study, Kyra's pedagogical approach was found to be unique in that it provided increased opportunities for the development and consolidation of strategic processes that are essential for independent thinking and learning. It was found that these opportunities were fostered through a balanced provision of relationships, play and environments. Collectively, these elements created a context in which scientific and everyday concepts could connect. The children in this classroom were observed to demonstrate higher order thinking skills more often and seemingly more independently than the children in the other classrooms.